Immunity-related genes in Ixodes scapularis—perspectives from genome information - Smith, Alexis A.; Pal, Utpal (Frontiers in Cellular and Infection Microbiology, 2014)
Ixodes scapularis, commonly known as the deer tick, transmits a wide array of human and animal pathogens including Borrelia burgdorferi. Despite substantial advances in our understanding of immunity in model arthropods, including other disease vectors, precisely how I. scapularis immunity functions and influences persistence of invading pathogens remains largely unknown. This review provides a comprehensive analysis of the recently sequenced I. scapularis genome for the occurrence of immune-related genes and related pathways. We will also discuss the potential influence of immunity-related genes on the persistence of tick-borne pathogens with an emphasis on the Lyme disease pathogen B. burgdorferi. Further enhancement of our knowledge of tick immune responses is critical to understanding the molecular basis of the persistence of tick-borne pathogens and development of novel interventions against the relevant infections.